Pirfenidone: An Encouraging Therapeutic Approach For Enhancing Lateral Spinothalamic Tract Function After Spinal Cord Compression Injury - Wazir, Noman Ullah; Humayun, Ambereen; Javaid, Irum; Amir, Asma; Khattak, Nayyab; Iftikhar, Ayesha (Journal of Rawalpindi Medical College, 2024)
Abstract Objective: The objective of this study was to investigate whether intraperitoneally administered pirfenidone could enhance the sensory activity of the lateral spinothalamic tract in rats after compression injury to the spinal cord. Method: Injury induction at the T7 spinal cord level was achieved using a 70-gram force aneurysm clip in rats. The study involved three groups: Group A received a daily placebo, Group B received a daily dose of 200 mg/kg pirfenidone, and Group C received a daily dose of 500 mg/kg pirfenidone. Subsequently, each group was further divided into two sub-groups, labelled as groups 1 (14 days experimental duration) and 2 (28 days experimental duration), each consisting of 5 rats. On the last day of the experiment, lateral spinothalamic tract activity as pain and temperature sensations in the hind limbs of all rats were assessed. Results: Scores from the Von Frey test, hot plate test, and acetone drop test exhibited statistical differences both between and within groups. In comparison to non-pirfenidone-treated spinal cord injury groups, those treated with pirfenidone demonstrated a decline in all these scores. Conclusion: Pirfenidone with its anti-fibrotic and anti-inflammatory action, is likely to enhance the functionality of the lateral spinothalamic tract following spinal cord injury.